Basic Science - Clinical Correlation Exercise Using a High Fidelity Simulator - David Wald; James Heckman; Jane Cripe (Association of American Medical Colleges, 2010)
Abstract Introduction This simulation module contains two exercises that were developed for the Temple University School of Medicine Doctoring course (for preclinical medical students) to help bridge the gap between basic science knowledge and its application to patient care. The general purpose of the module is to provide a platform for medical students to review and reinforce basic science principles of cardiac physiology as it relates to a clinical case of complete heart block (CHB) or ventricular tachycardia (VT). Both cases were developed through a collaborative effort between the Department of Emergency Medicine, Department of Physiology, and the Institute for Clinical Simulation and Patient Safety at the Temple University School of Medicine. Methods The cases are designed to incorporate a high-fidelity simulator (SimMan) which allows the student to perform an initial physical examination. Faculty members primarily serve as facilitators guiding the discussion and reinforcing various basic concepts. Results Postexercise evaluations of both cases have uniformly been very positive. Numerous students have commented on the substantial educational value of the cases, as well as the opportunities provided to enhance their knowledge of basic science, and integrate the concepts and knowledge in a clinical setting. Discussion Initiatives such as this serve a number of purposes. First and foremost, it offers students a unique experience to learn in a small-group setting (seven or eight students to two faculty members) with both a basic science and clinical faculty member. In addition, this exercise allows for collaboration between basic scientists and clinicians in a way that builds collegial relationships. In many ways, the two cases complement each other while focusing on different ends of the arrhythmia spectrum.